PENGARUH PENAMBAHAN SERAT GALVALUM PADA BETON RINGAN DENGAN TEKNOLOGI FOAM TERHADAP KUAT LENTUR, TOUGHNESS, DAN STIFFNESS - Purnawan Gunawan; Wibowo Wibowo; Dewana Istiyan Primasatya (Matriks Teknik Sipil, 2014)
surrounding environment. Lightweight concrete foam is made of concrete without coarse aggregate in the mix with added foam material agent (liquidfoam). The purpose of this study was to determine how much influence the addition of fiber galvalum the flexural strength, toughness, and stiffnessof lightweight concrete foam galvalum fiber. The method used in this study is an experimental method that is then theoretically analyzed. Value offlexural strength on fiber 0 %, 0.25 % , 0.5, and 1 % , respectively, 104.28 t/m2 ; 110.31 t/m2 ; 182.99 t/m2 , and 134.98 t/m2 , at 0.5fibers % an increase in flexural strength of 75.48 % . Toughness values occurred in 0.5 % with the addition of fiber 1407 Nmm value unchangedat 121.92 % . Galvalum stiffness with the fiber content of 0% , 0.25 % , 0.5 % , 1 % were tested at 28 days is 5001.65 N / mm ; 7277.67N / mm ; 8472.88 N / mm and 7957.14 N / mm. The addition of the fiber content of 0.5 % yield Stiffness value of 69.40 % compared tothe lightweight foam concrete without fibers.